(3GdZQjHjfs - (3CMeO Hf eMeO Hf YHO GdQMef GdHGTGfj GdgQhj, CHh YHjO, J (B401 (3g` s ((3eMeO Hf eMeO GdbfWQi s)
(3ChdgG (B:s
(3bGd CHh YHjO CMeO Hf eMeO Hf eMeO GdgQhi bGd SHMGf ef dg ai cd TF TGgO HCfg Bdg hGMO cJGH GdgeRI HSe Gddg GdQMef GdQMje bdJ GdGda YfO GdYQH HGH GdgeRI eY GdHGA s
(3BNQgG (B:s
(3HHGH GdjGA eY GdgGA hCdGo jSge GdHdO GdPi dGYde HgG Je GdcJGH s
(3cJHJ HYV GdGdaX HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B210s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1209s
Keywords: (3GdMOjK h GdeUWdMs